Risk Monitoring and Control in Audit Firms: A Research Synthesis - Bedard, Jean C.; Deis, Donald R.; Curtis, Mary B.; Jenkins, J. Gregory (Auditing : a journal of practice and theory, 2008)
This paper summarizes the research literature related to audit firm quality control, with a dual purpose: (1) to provide information on the current state of knowledge with regard to the ways in which audit firms monitor and control firm-level risk; and (2) to identify specific areas in which there is currently insufficient research. We review literature on a number of specific topics under the overall heading of firm-level risk monitoring and control, including: client acceptance/continuance procedures, auditor independence (partner and firm rotation, employing former auditors, nonaudit services, partner compensation), electronic decision aids, consultation units, procedures for communicating weaknesses and taking corrective action, and review of engagement activities (including engagement quality reviews, peer reviews, and regulatory inspections). We conclude with a discussion of research relevant to the issue of whether smaller audit firms should be subject to the same level of quality control regulation as larger firms.